Effect of Thermal Neutron Irradiation on the Electrical Properties of Lead-Selenium Substituted S70Se30-XPbX Chalcogenide Glasses - Hajem, Mahmoud Y.; Jasim, Kareem A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
This study included the effect of thermal neutron radiation and partial replacement of selenium with lead for S70Se30-xPbx alloy samples with different lead concentrations (x = 0 and 5) prepared by the melting point technique. The samples were examined before and after thermal neutron irradiation for seven days with Am241−Be9 radioactive source, with a radiation dose of . Continuous electrical conductivity analysis revealed changes in all samples, attributed to the rearrangement of the crystal structure caused by radiation-induced disturbances. These changes led to modifications in the electrical properties of the irradiated samples compared to the non-irradiated ones. compared to the non-irradiated ones. Three different conduction mechanisms were found. At low temperatures, the electron transition occurred via electron hopping between localized states close to the Fermi energy. At intermediate temperatures, the conduction occurred via electron hopping between localized levels between the tails of the conduction and valence bands. The electrons moved through extended levels within the two bands at high temperatures. The results indicated that the calculated densities of extended, localized, and Fermi-level states underwent significant changes due to thermal neutron radiation and partial substitution